Penerapan Flipped Classroom Dalam Pembelajaran Daring (Synchronous Dan Asynchronous) Di Jurusan Pendidikan Ekonomi Universitas Siliwangi - Bakti Widyaningrum; Edi Fitriana Afriza (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2021)
The flipped class method was implemented to observe the difference of student scores before and after applied. The method of research was classroom action research in two cycles. The population were Department of Economics Education’s students of Siliwangi University. Technique sampling in this study was purposive sampling with a total sample 77 students. Data analysis was carried out in two ways, descriptive analysis and t-test comparison test. The average score of student before implementing flipped classroom method was 69.247, after the first cycle the student pretest score was 69.714, and the average student score at the end of the second cycle was 80.104. The t-statistic value was 15,895 greater than 1,99167 (t table 5%). Based on these results, it can be concluded that student scores has increased significantly after the flipped classroom implemented in online learning (synchronous and asynchronous) at the Department of Economics Education, University of Siliwangi